2012
DOI: 10.1371/journal.pone.0034860
|View full text |Cite
|
Sign up to set email alerts
|

Deregulation of CREB Signaling Pathway Induced by Chronic Hyperglycemia Downregulates NeuroD Transcription

Abstract: CREB mediates the transcriptional effects of glucose and incretin hormones in insulin-target cells and insulin-producing β-cells. Although the inhibition of CREB activity is known to decrease the β-cell mass, it is still unknown what factors inversely alter the CREB signaling pathway in β-cells. Here, we show that β-cell dysfunctions occurring in chronic hyperglycemia are not caused by simple inhibition of CREB activity but rather by the persistent activation of CREB due to decreases in protein phophatase PP2A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 73 publications
0
8
0
Order By: Relevance
“…Alternatively, the FMD may increase survival of newly-differentiated neurons, as observed in the dentate gyrus of alternate day-fed rodents (Lee et al, 2002; Mattson et al, 2001). The observed improvements in cognitive performance in the FMD cohort might be affected by an the increase in neurogenesis mediated by PKA/CREB-dependent regulation of NeuroD1 (Cho et al, 2012; Sharma et al, 1999), which is known to increase neuronal survival and differentiation of hippocampal progenitors (Roybon et al, 2009), enhance functional integration of new neurons, and alleviate memory deficits in a mouse model of Alzheimer’s disease (Richetin et al, 2015). …”
Section: Resultsmentioning
confidence: 99%
“…Alternatively, the FMD may increase survival of newly-differentiated neurons, as observed in the dentate gyrus of alternate day-fed rodents (Lee et al, 2002; Mattson et al, 2001). The observed improvements in cognitive performance in the FMD cohort might be affected by an the increase in neurogenesis mediated by PKA/CREB-dependent regulation of NeuroD1 (Cho et al, 2012; Sharma et al, 1999), which is known to increase neuronal survival and differentiation of hippocampal progenitors (Roybon et al, 2009), enhance functional integration of new neurons, and alleviate memory deficits in a mouse model of Alzheimer’s disease (Richetin et al, 2015). …”
Section: Resultsmentioning
confidence: 99%
“…7 days of chronic in vitro treatment of islets with FKN led to increased expression of PDX1, NeuroD, HIF-1α and insulin (Figure 6L), and these genes were all down regulated in the CX3CR1 KO islets (Figure 3H). Recently, it has been shown that beta cell dysfunction induced by HFD or free fatty acid treatment, is, at least partially, mediated by the induction of inducible cyclic AMP early repressor (ICER-1) (Cho et al, 2012; Favre et al, 2011; Hussain et al, 2000; Zhou et al, 2003). Interestingly, ICER-1 expression was highly induced in the CX3CR1 KO islets (Figure 6M) and FKN treatment abolished palmitate-induced induction of ICER-1 mRNA in Min6 cells (Figure 6N).…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, the current data demonstrating that ICER mRNA and protein expression were elevated in diabetic SIECs in connection with a reduction in a number of CRE target genes, such as NURR1 , IRS2 and VEGF , give credence to the aforementioned proposition. These findings are not unique to the diabetic SIECs as a persistent elevation of CREM/ICER and the concomitant suppression of gene transcription was also evident in other pathological conditions and cell types, such as hypercortisolemia ( Shepard et al, 2005 ), hypercatecholemia ( Lewin et al, 2009 ; Leopold et al, 2007 ) and hyperglycemia ( Cho et al, 2012 ), in addition to angiotensin-II-treated cardiomyocytes ( Ding et al, 2005 ) or oxidized LDL-treated insulin-secreting cells ( Favre et al, 2011 ).…”
Section: Discussionmentioning
confidence: 96%